Техногенные минерально-сырьевые ресурсы - Комаров М. А.; Михайлов Б. К.; Киперман Ю. А.; Боков В. Г.; Алискеров В. А.; Григорьев Н. П.; Заверткин В. Л.; Каменев Е. А.; Милетенко И. Н.; Панин О. Н.; Селифонов Е. М.; Поярель А. А.; et al. (Алматы, ВИЭМС, 2003)
В фонде НТБ ТПУ отсутствует